Projecting cropping patterns around Poyang lake and prioritizing areas for policy intervention to promote rice: A cellular automata model. (May 2018) - Zhang, Rui; Tian, Qing; Jiang, Luguang; Crooks, Andrew; Qi, Shuhua; Yang, Ruixin
Abstract: Rural households' cropping choices are increasingly influenced by non-farm activities across the developing world, raising serious concerns about food security locally and globally. In China, rapid urbanization has led to agricultural decline in some regions. To stimulate agriculture, the Chinese government has recently increased its effort in farmland consolidation by providing special support to large farms in an attempt to address land-use inefficiency associated with small farming operations in rural areas. Focusing on the Poyang Lake Region (PLR), we develop an empirical Cellular Automata (CA) model to explore future agricultural land use and examine the impact of farmland consolidation, with the intention of providing insight for policy to effectively promote food production. The PLR is an important rice producing area for Jiangxi Province and China. In the PLR, rice can be grown once a year on a plot, called one-season rice, or twice a year on the same plot, called two-season rice. Our CA model simulates the transition between one-season and two-season rice. We use the modeling results to identify five types of areas (zones) where rice cultivation is (i) relatively stable for one-season rice, (ii) more likely to be one-season rice, (iii) of equal probability for either type, (iv) more likely to be two-season rice, and (v) relatively stable for two-season rice. In addition we explore the characteristics of these zones in terms of biophysical and geographical features to offer a detailed analysis and discussion of how the government may prioritize areas for interventions to sustain rice production amid urbanization. Our analysis also shows some positive effect of farmland consolidation on increasing rice production in the study area.